Dietary Factors in Nonalcoholic Fatty Liver Disease: Impacts on Human and Animal Health-A Review - Echeverria-Morgado, J (Institute of Genetics and Animal Biotechnology of the Polish Academy of Sciences, 2023)
Non-alcoholic fatty liver disease (NAFLD) is defined as a clinical syndrome characterized by excessive fat accumulation in liver, predominantly influenced by dietary choices. This study provides an extensive quantitative literature analysis on dietary influences on NAFLD. Bibliometric data were collected through the search string TOPIC = (“NAFLD*” OR “nonalcoholic fatty liver*” OR “non-alcoholic fatty liver*”) AND TOPIC = (“diet*” OR “nutrition*” OR “food*” OR “feed*”), which yielded 12,445 publications indexed within the Web of Science Core Collection. Utilizing VOSviewer software, term maps were generated to visually illustrate recurring phrases alongside citation data. The literature, which has seen exponential growth since the 2010s, predominantly consists of original articles, with a ratio of 4.7:1 compared to reviews. Notably, the significant contributors to this field were China and the United States. The majority of publications were found journals specialized in Gastroenterology & Hepatology, Nutrition & Dietetics, Biochemistry & Molecular Biology, Endocrinology & Metabolism, and Pharmacology & Pharmacy. Key dietary compounds/compounds classes such as resveratrol, polyphenols, curcumin, berberine, quercetin, flavonoids, omega-3 fatty acids, docosahexaenoic acid (DHA), genistein, and palmitic acid were frequently mentioned and cited. Many of them were demonstrated to have some potential benefits on NAFLD, both in human and animal studies. © 2023, Institute of Genetics and Animal Biotechnology of the Polish Academy of Sciences. All rights reserved.